Extracción del aceite esencial de Lavanda (lavándula angustifolia), mediante la metodología de arrastre de vapor. - Palacios Rosero, Omar Fabricio (2022)
This investigation was carried out to extract essential oil from lavender (Lavándula angustifolia) using the steam drag method, assisted by an essential oil extractor with the following operating conditions: time: 60, 105, 150 min, and the ratio of material / distilled water: 1;3, 1;4,1;5. The process temperature was maintained based on the boiling temperature of the water. A total of 17 shifts were carried out where the essential oil was recovered with Clevenger trap equipment, then 2 g of Na2SO4 was added for half an hour, then the sample was decanted and filtered; finally, it was packed in dark bottles. In addition, a Design Expert 8.0.6 statistical program (Stad-Ease Inc., Minneapolis, USA) was used for data processing with a response surface design, where an essential oil characterization was carried out using CG-MS with a mass detector on an Agilent Technologies 5975 inert XL MSD with Triple-Axis Detector GC-MS benchtop Agilent mass spectrometer. The antioxidant capacity of the oil was determined using two methods: FRAP- ABTS, giving a result of 101.23 µmol ET /g and 84.24 µmol Fe2+/g. An antimicrobial analysis was also developed, being the microorganism Pseudomonas aeruginosa ATTC10145 the one that showed the most significant resistance, presenting a MIC of 5%. Finally, the execution of the statistical program also allowed the researchers to validate the experimental value, giving 0.6499% of the oil yield obtained, similar to that predicted.